HYBRID VIGOR OF CUCUMBER HYBRIDS DEVELOPED LOCALLY WHICH SUITABLE FOR OPEN FIELD CULTIVATION - & Almashhadani, AL-Jebory (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This experiment was carried out during two seasons; the first season 2016 included the planting of cucumber seeds from different global origins, which symbolized P1 and P2-P10 in a plastic house with (506 m2) area, at Yusufiya – Baghdad to produce hybrids. During Spring season 2017 the genotypes seeds were planted (10 parents and 27 single cross hybrids with codes F1 and F2-F27 and three common commercial control hybrids with codes C1, C2 and C3) according RCBD design with three replicates, The genotype P5 was superior in the branches number per plant (9.67) and number of leaves per plant (220.33) as well as in total yield of experimental unit 18.03 kg, The hybrid F17 (P5×P9) took lowest number of days number until first female flower appearance (34.00 days) and number of days until first harvest (37.67 days), as well as it produce the highest fruit weight 178.747 gm, the most of hybrids had significant heterosis, the hybrid F23 had the highest positive hybrid vigor in number of leaves per plant (73.03%), the hybrids F4, F17 and F19 had negative heterosis in number of days until first female flower appearance, eight hybrids had positive hybrid vigor in weight of fruit but 16 hybrids had heterosis in experimental unit yield and the highest value obtained from F27 67.77%, while in control hybrid vigor, 15 hybrids had the superiority in numbers of branches so the highest value obtained from F3 53.96%, also it had the highest value of control hybrid vigor in number of leaves per plant 93.21%, the hybrid F27 had significant control hybrid vigor in experimental unit yield 66.79%.